A review of fibropapillomatosis in Green turtles (Chelonia mydas). (June 2016) - Jones, K.; Ariel, E.; Burgess, G.; Read, M.
Highlights: Fibropapillomatosis (FP), an emerging disease in green turtles, is reviewed. Chelonid herpesvirus 5 is the likely aetiological agent of FP. The route of transmission and conditions facilitating lesion development are uncertain. High prevalence of FP is observed in areas of reduced water quality. A multi-factorial interplay between a range of factors is likely to be occurring. Abstract: Despite being identified in 1938, many aspects of the pathogenesis and epidemiology of fibropapillomatosis (FP) in marine turtles are yet to be fully uncovered. Current knowledge suggests that FP is an emerging infectious disease, with the prevalence varying both spatially and temporally, even between localities in close proximity to each other. A high prevalence of FP in marine turtles has been correlated with residency in areas of reduced water quality, indicating that there is an environmental influence on disease presentation. Chelonid herpesvirus 5 (ChHV5) has been identified as the likely aetiological agent of FP. The current taxonomic position of ChHV5 is in the family Herpesviridae, subfamily Alphaherpesvirinae, genus Scutavirus . Molecular differentiation of strains has revealed that a viral variant is typically present at specific locations, even within sympatric species of marine turtles, indicating that the disease FP originates regionally. There is uncertainty surrounding the exact path of transmission and the conditions that facilitate lesion development, although recent research has identified atypical genes within the genome of ChHV5 that may play a role in pathogenesis. This review discusses emerging areas where researchers might focus and theories behind the emergence of FP globally since the 1980s, which appear to be a multi-factorial interplay between the virus, the host and environmental factors influencing disease expression.